(untitled) (Journal of Philosophy Culture and Political Science, 2021)
Political participation as an institution of the political system of modern society correlates with the concept of the democratization factor of state life. The architecture of political participation - the activity of people, their political actions aimed at exercising control over power or exerting pressure on power, is the main criterion for evaluating the political process. The purpose of this article is a political science analysis of the conceptual aspects of the institution of political participation of citizens in the context of globalization. The aim predetermined the main directions and ideas of the present research: political participation as an object of political science analysis is analyzed in the paradigm of historical concepts of foreign scientists from developed democracies, taking into account their transformation in the political processes of young democracies. The global transformation of political systems has had a significant impact on the development of the institution of political participation as a factor in the democratization of society. The challenges of globalization cause the urgent need to modernize the process of transformation of the political systems of modern states. On the basis of modern scientific methods and a wide range of foreign sources and carried out an analysis of the worldwide discussion about the essence and importance of political participation for the development of democracy. Application of general scientific and special methods allowed to carry out a comprehensive analysis of the process of political participation in the context of democratization of society in different states at all stages of the evolution of the object under study. The results of the study expand the boundaries of scientific knowledge about the phenomenon of political development, value and behavioral aspects of political transformation. The materials of the study can serve as the basis both for conceptualizing the theoretical basis for specific practical political decisions, and for modeling the general scenario of development in modern states of the political process in general, and political participation in particular. Keywords: political participation, political process, transformation, political science analysis, democracy, globalization.